The Implementation of Portfolio Assessment to Increase Critical Thinking Ability for High School Students on Human Coordination System Material - Tiara Linanti, Annisa; Ridlo, Saiful; Bintari, Siti Harnina (Universitas Negeri Semarang, 2021)
Critical thinking has an essential role in the development of 21st-century skills to form students who have a deep understanding of the subject being studied. The use of portfolio assessment is believed to be a means of mastering a subject. This study was aimed to analyze whether the implementation of portfolio assessment in Biology learning in human coordination systems material can improve students' critical thinking skills. This study used a pretest and posttest control group design. Based on the results of the analysis, it was found that the means posttest score of students' critical thinking skills in the experimental class was 78.28, and the control class was 63.36. The Independent Sample T-Test showed a significant mean difference between the experimental class and the control class. The improvement of critical thinking skills by implementing portfolio assessment was better than the control class. The regression test showed that the contribution of the portfolio assessment to the improvement of critical thinking skills was 19.1%. The results of the analysis showed that the portfolio assessment distributed students in three categories of critical thinking skills were 59.4% in the enough category, 31.3% in the good category, and 9.4% in the very good category. The conclusion is that the implementation of portfolio assessment has a positive effect on increasing students' critical thinking skills in the human coordination system material.